English For Islamic Banking: What English Need of Indonesian Syariah Bank Employees in Bengkulu City - Kurniawan, Yuda Septian; Hakim, M. Arif Rahman; Yanto, Syafri (Linguists : Journal of Linguistics and Language Teaching, 2024)
This research aims to determine the English language needs of Indonesian sharia bank employees in Bengkulu City. The research design in this research is qualitative research, while the research subjects are 10 Indonesian sharia bank employees in Bengkulu City. This research data was collected using interviews technique. Research findings show that: (1) Islamic bank employees need English language materials related to banking, accounting and computer applications; and (2) Islamic bank employees need more reading skills than listening, speaking and writing skills because they work more with written documents in English. Bank employees also work with computer programs, so all instructions and terms on the computer use English. Based on these needs, employees should havea good pronunciation in banking, accounting and computer English terms. They also need skills in correspondence via electronic mail or email.